Measurements of sensible heat flux in katabatic wind at Mizuho Station, East Antarctica - Kobayashi, Shun'ichi; Ishikawa, Nobuyoshi; Ohata, Tetsuo; Kawaguchi, Sadao (1982)
P(論文) A study was made of transfer of heat under strong surface inversion observed in 1980 at Mizuho Station, East Antarctica. Two sonic anemothermometers were used for direct measurements of eddy heat flux divergence or convergence between the levels of 3 and 30m above a snow field when skies were clear and weak katabatic winds were blowing at a low level. We obtained the following results : When the surface cooling is predominant, the air layer between the snow surface and 30m has a structure in which at the surface a downward sensible heat flux compensates radiative cooling, and at 30m any sensible heat flux remains insensible until a gravity wave comes about from shear instability. The sum of values of radiative flux divergence between the snow surface and the top of a 30-m-high tower, and values of sensible heat flux divergence or convergence between the levels of 3 and 30m, shows a discrepancy in comparison with the actual cooling or warming rate. This discrepancy suggests that the amounts of advection and phase change are not neglegible concerning their effects on the rate of cooling or warming by radiative heat plus sensible heat which accompanies the developments of low katabatic flow. departmental bulletin paper